1989
DOI: 10.1523/jneurosci.09-04-01213.1989
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brain stem of the ferret: some effects of rearing with a unilateral ear plug on the cochlea, cochlear nucleus, and projections to the inferior colliculus

Abstract: To examine the influence of acoustic experience on the development of the mammalian auditory brain stem, darkly pigmented ferrets were reared with a plug inserted in the right outer ear. The plugs were first inserted on postnatal day 23-34 and produced a variable, frequency-dependent attenuation of up to 60 dB. Between 3-15 months after the ear plug was begun, animals were prepared for physiological recording and injection of wheat germ agglutinin-HRP (WGA-HRP) in the left inferior colliculus (IC). The plug wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
58
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 72 publications
(110 reference statements)
5
58
1
Order By: Relevance
“…The concha of the external ear was filled with Otoform-K 2 silicone impression material (Dreve Otoplastik, Unna, Germany). The sound attenuation produced by these earplugs has previously been estimated, using auditory brain stem response audiometry, to be ϳ40 dB across a broad range of frequencies (Moore et al 1989). Acoustical measurements from a number of different model ferret ears created from Otoform imprints of variously sized real ears confirmed that the earplugs produced 40 -50 dB of attenuation at frequencies of Ͼ3.5 kHz, which gradually rolled off at lower frequencies.…”
Section: Experimental Designmentioning
confidence: 92%
See 2 more Smart Citations
“…The concha of the external ear was filled with Otoform-K 2 silicone impression material (Dreve Otoplastik, Unna, Germany). The sound attenuation produced by these earplugs has previously been estimated, using auditory brain stem response audiometry, to be ϳ40 dB across a broad range of frequencies (Moore et al 1989). Acoustical measurements from a number of different model ferret ears created from Otoform imprints of variously sized real ears confirmed that the earplugs produced 40 -50 dB of attenuation at frequencies of Ͼ3.5 kHz, which gradually rolled off at lower frequencies.…”
Section: Experimental Designmentioning
confidence: 92%
“…The remaining three ferrets provided control data for the earplugging experiment. The methods used to train the ferrets have been described in detail in previous reports (Kacelnik et al 2006;Nodal et al 2008) and are outlined briefly below.…”
Section: E T H O D Smentioning
confidence: 99%
See 1 more Smart Citation
“…More recent research provides further support for changes in auditory brain function (Moore et al 1999;King et al 2000;Tucci et al 2001). However, while the effects of visual form deprivation and interocular misalignment in infancy are profound and relatively well understood, the early, mild, asymmetric conductive hearing loss produced by OME (Kokko 1974;Gravel and Wallace 2000; or, experimentally, by occlusion of the ear canal (Knudsen et al 1984;Moore et al 1989Moore et al , 1999King et al 2000) or malleus removal (Cook et al 2002) seems to exert a more subtle influence on central auditory processing.…”
Section: Introductionmentioning
confidence: 96%
“…1A) and incidence (Hogan et al 1997(Hogan et al , 1998Paradise et al l997;Hogan 1999) of otitis media with effusion (OME, also known as ''glue ear'') in early childhood has generated much speculation concerning its effect on the development of the human auditory system and on language acquisition and perception. Concern about the effects of OME as a form of auditory deprivation was further heightened by research from animal studies, first in the visual system (Wiesel and Hubel 1965;Sherman and Spear 1982) and later in the auditory system (Knudsen et al 1984;Moore et al 1989), showing that abnormal sensory experience could produce long-term changes in the structure and function of the primary brain circuits responsible for vision and hearing. More recent research provides further support for changes in auditory brain function (Moore et al 1999;King et al 2000;Tucci et al 2001).…”
Section: Introductionmentioning
confidence: 99%